Systemic Breakdowns in Safety Defenses: An HFACS Analysis of Fatigue-Related Accidents and Organizational Failures in Coal Mining (2020–2024) - Sari Febryanti Wibisono; Robiana Modjo (Jurnal Kesehatan Komunitas Indonesia, 2026)
Background: Coal mining is among the industries with the highest risk of occupational accidents due to the complex interactions among humans, machines, and the environment. Objective: This study aims to analyze the causal factors of occupational accidents in the coal mining sector by reviewing 25 incident investigation reports from 2020 to 2024. Methods: A descriptive analysis using the Swiss Cheese Model and the Human Factors Analysis and Classification System (HFACS) was employed to identify systemic patterns and contributing factors. Results: The results indicate an increasing trend in incidents, rising from 5 cases (2020) to 10 cases (2024), with total material losses exceeding Rp 1.2 billion. Severity classification: Near Miss 2 cases (8%), Property Damage 16 cases (64%), First Aid Injury 5 cases (20%), and Lost Time Injury 2 cases (8%). The HFACS analysis identified failures at four levels: organizational influences (production pressure, inconsistent policies), inadequate supervision, unsafe conditions, and unsafe operator actions. Fatigue was identified as a consistent contributing factor in 100% of cases, manifesting as microsleep, insufficient sleep duration, and dishonesty in reporting physical condition. The gap analysis indicates that the simultaneous failure of multiple barriers is not due to random factors but rather systemic failures rooted in an organizational culture that prioritizes production. Conclusion: The occupational accidents that occurred were not caused by random factors, but rather a series of systemic failures culminating in operator fatigue. This study recommends an integrated approach to prevent incidents, which includes system strengthening (such as the utilization of monitoring technology and roster optimization), cultural transformation (from a blame culture to a learning culture), and consistent policy implementation with clear accountability across all organizational levels.